Pulses for food and nutritional security: The technology perspective - Roy, Devesh; Kishore, Avinash; Joshi, P. K.; Mishra, B. (The Indian Journal of Genetics and Plant Breeding, 2017)
Pulses though extremely important from a food security and nutrition perspective in India have lagged behind cereals and have been moved increasingly to marginal environments. The persistent demand supply gap in pulses poses several challenges including technological ones that stem from movement of pulses to difficult environments and its place in relation to the competing crops. Technologies in pulses have evolved in line with the needs such as short duration to meet intercropping requirements. Given the long history of technology development that lags behind principal crops marked by near absence of private sector in R&D in pulses, it may be time to rethink and try demand pull systems of research with Advance Marketing Commitments along the lines suggested for vaccines.